PENDAMPINGAN DALAM PENGEMBANGAN MEDIA PEMBELAJARAN BAHASA ARAB PADA SEKOLAH MITRA DI KOTA MATARAM NUSA TENGGARA BARAT - nurjanah nurjanah; M. Syahrul Izomi; Husnan Husnan (Universitas Muhammadiyah Mataram, 2024)
Some of the problems we found are, learning media only in the form of textbooks, all forms of Arabic language learning use the same media, while one media is not necessarily suitable for training Arabic language skills with different varieties, have not been able to develop learning media due to the busyness of each teacher, lack of understanding and knowing how to make media in accordance with learning objectives, needs and circumstances of students, and lack of funds to develop learning media. The purpose of this activity is to provide an introduction to teachers about Arabic learning media and its types, help teachers create and develop Arabic learning media, and help teachers apply learning media in learning activities. The implementation method in this activity is a group-based method and mentoring. Mentoring activities in Arabic Learning Media Development in Partner Schools are running smoothly. This activity takes place in each partner school in turn. This activity is needed by Arabic language teachers to support the Arabic language learning process.